2020
DOI: 10.1111/ijtd.12175
|View full text |Cite
|
Sign up to set email alerts
|

When innovation in education works: stimulating teachers' innovative work behaviour

Abstract: The twenty-first century labour market requires employees that proactively shape innovations and solve complex problems. Professionals in the education sector are expected to perform innovative behaviour that not only entails the generation, but also the realization and sustainable implementation of new ideas. In a sample of 458 employees in Dutch secondary and higher vocational education (abbreviated in Dutch to MBO and HBO, respectively), this study investigated the relation between environmental factors (na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 68 publications
3
31
0
3
Order By: Relevance
“…For the IWB scale, the results in F I G U R E 3 Structural model for the study variables validity. This confirms the observations of prior studies on higher education (Ayoub et al, 2021;Lambriex-Schmitz et al, 2020a, 2020b that consider IWB a multidimensional concept.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…For the IWB scale, the results in F I G U R E 3 Structural model for the study variables validity. This confirms the observations of prior studies on higher education (Ayoub et al, 2021;Lambriex-Schmitz et al, 2020a, 2020b that consider IWB a multidimensional concept.…”
Section: Discussionsupporting
confidence: 90%
“…Shanker et al (2017) confirmed the significant positive effect of an organizational culture of innovation on IWB Lambriex-Schmitz et al (2020b). confirmed prior exposure to innovation as a key predictor for all phases of IWB.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…At the same time, higher education is the main responsibility for training flexible, open to new technologies, creative specialists (Bystrova, 2015). However, universities are often criticized for their conservatism, lack of innovative educational programs that will meet the needs of the labor market, students, and society as a whole (Lambriex-Schmitz et al, 2020;Stukalenko et al, 2013). To solve this issue, higher education institutions are encouraged to create new educational and institutional strategies for training specialists, developing their innovative abilities, and actively engaging in the development and implementation of innovations (Lambriex-Schmitz et al, 2020;Fedorov, 2021).…”
Section: Introductionmentioning
confidence: 99%